Antioxidant, genoprotective and hepatoprotective activities of Panus giganteus (berk.) corner / Wong Wei Lun - Wong, Wei Lun (2012)
Panus giganteus, a culinary and medicinal mushroom consumed by selected indigenous communities in Malaysia is currently being considered for large scale cultivation. This study was performed to investigate the medicinal potential of P. giganteus fruiting bodies and wheat grains fermented by P. giganteus including antioxidant, genoprotective and hepatoprotective properties. Ethanol extracts of P. giganteus fruiting bodies, wheat grains fermented by P. giganteus and unfermented wheat grains exhibited moderate antioxidant properties by virtue of DPPH free radical scavenging activity, reducing power, antioxidant capacity and inhibition of lipid peroxidation. The extracts also contained moderate amounts of phenolic compounds. Fruiting bodies were more potent than fermented and unfermented wheat grains in protecting DNA of peripheral blood mononuclear cell (PBMC) against hydrogen-peroxide (H2O2)-induced damage. However, all the extracts had comparable activities to repair DNA damaged by H2O2. Hepatoprotection studies indicated that P. giganteus fruiting bodies were able to prevent and treat liver injury induced by thioacetamide (TAA). Administration of P. giganteus lowered the elevated liver body weight ratio, also restored the levels of serum liver biomarkers and oxidative stress parameters comparable to the standard drug silymarin. Gross necropsy and histopathological examination further confirmed the hepatoprotective effects of P. giganteus. vi This is the first report on the medicinal properties of locally grown P. giganteus. Overall, consumption of P. giganteus fruiting bodies or wheat grains fermented by P. giganteus have genoprotective and hepatoprotective effects against injury induced by oxidative stress